Study on the nonlinear mechanical behaviour of an umbilical under combined loads of tension and torsion. (15th October 2021) - Yang, Zhixun; Su, Qi; Yan, Jun; Wu, Shanghua; Mao, Yandong; Lu, Qingzhen; Wang, Hualin
Abstract: Umbilical is preferred as a remote controlling device in the subsea production system during the offshore oil and gas exploitation, which is composed of some functional and strengthening components in the form of helically wound structure. There is an obvious tension-torsion coupling effect due to helical structural characteristic, and the radial behavior of core structure of an umbilical involves nonlinearity because of polymer material and space gaps between components. A methodology calculating the nonlinear tension-torsion coupling effect is proposed in this paper. The theoretical description of the tension-torsion coupled behavior of the helically wound structure is derived, and the tension-torsion stiffness matrix expression with the parameter, the radial stiffness of the core structure of the umbilical, is obtained. Then, a semi-analytical calculation methodology of the tension-torsion stiffness of the umbilical is further established. Furthermore, a practical case of an umbilical is given, the nonlinear stiffness of tension is calculated through the established calculation methodology. Meanwhile, the tensile test of this umbilical is conducted and the testing datas verify the correctness of above results. Finally, the nonlinear tension-torsion coupling mechanical behavior of an umbilical is performed, which can provide a reasonable reference for the design and analysis of umbilicals used in deep water. Highlights: The tension-torsion coupling effect of the helically wound structure is analyzed, and the tension-torsion stiffness matrix expression of the umbilical is proposed. The radial nonlinear mechanical behaviour of core structure of an umbilical due to polymer material and space gaps between components is studied. The semi-analytical calculation methodology of the tension-torsion nonlinear coupling stiffness of the umbilical structure is proposed. A tensile experimental test of an umbilical structure is copied with to describe the nonlinear tensile mechanism of the structure. The proposed calculation methodology of the tension-torsion nonlinear coupling stiffness of the umbilical can provide a reasonable reference for the design and analysis of umbilicals with a high level of safety.